A systematic review of cancer waiting time audits. Issue 1 (3rd February 2005) - Lewis, R; Collins, R; Flynn, A; Dean, M Emmans; Myers, L; Wilson, P; Eastwood, A
Abstract : A summary of a systematic review of clinical audits of cancer referrals in England and Wales